Supermarket purchases and the dietary patterns of households in Guatemala - Asfaw, Abay (International Food Policy Research Institute, 2007)
Very limited empirical analyses are done on evaluating how changes in the retail environment affect diet and health status of consumers, especially in developing countries. The major objective of this study is to shed some light on some of these neglected but crucial issues. The study examines the impact of supermarket purchases on dietary practices (defined as the calorie share of different food groups) of Guatemalan households using the 2000 Guatemalan household survey. I use an instrumental variable method to take into account the potential endogeneity of the supermarket-purchase variable in the calorie share equations.... The results of the study reveal that supermarket purchases increase the share that highly and partially processed food items, such as pastries, cookies, crackers, chocolate, ice cream, and so forth, make of total calories, at the expense of staple food items such as corn and beans. Since most processed foods contain disproportionately high amounts of added fat, sugar, and salt, and since supermarkets are expanding rapidly, different policy measures should be developed to ensure that supermarkets have a "healthier" impact on diets.